Active protection for photovoltaic DC‐boosting integration system during FRT. Issue 18 (2nd September 2019) - Jia, Ke; Chen, Jinfeng; Xuan, Zhenwen; Wang, Congbo; Bi, Tianshu
Abstract : Compared with traditional photovoltaic (PV) power plants, PV DC‐boosting integration system faces serious DC‐bus overvoltage problem due to its special structure during the fault ride‐through (FRT). Based on the unique power‐output features of PV array, the authors describe a design of coordinated control strategy for the converters in the PV DC‐boosting integration system to maintain a stable DC voltage during FRT process. In addition, existing FRT control scheme ineluctably lowers the performance of the line protection; thus, a combination strategy of the system control and the line protection is proposed to enhance the fault discrimination ability (especially the interphase fault). A detailed model of the PV DC‐boosting integration system is created in PSCAD/EMTDC; the simulation results show that the proposed method not only realises the smooth FRT process with a stable DC bus voltage but also can reliably identify the voltage sag caused by the transmission line faults.